2018
DOI: 10.1177/0954406218802928
|View full text |Cite
|
Sign up to set email alerts
|

Study on the critical loosening condition toward a new design guideline for bolted joints

Abstract: An understanding of conditions that trigger the loosening of bolted joints is essential to ensure joint reliability. In this study, a three-dimensional finite element model of a typical bolted joint is developed, and a new simulation method is proposed to quantitatively identify the critical transverse force for initiating loosening. This force is used to evaluate the anti-loosening capacity of bolted joints. Using the proposed simulation method, the effects of factors affecting critical loosening are systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Gong et al [101] FEA Developed a novel simulation method, including two stages to clearly monitor the real rotation-induced loosening.…”
Section: Local Slippage Accumulation Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Gong et al [101] FEA Developed a novel simulation method, including two stages to clearly monitor the real rotation-induced loosening.…”
Section: Local Slippage Accumulation Theorymentioning
confidence: 99%
“…Gong et al [22,23] found that it was difficult to identify the critical transverse force for initiating loosening using a traditional finite element simulation owing to stress redistribution. Therefore, they developed a novel simulation method that included two stages to clearly monitor the real rotation-induced loosening [101]. In the first stage, a large transverse force was initially applied to accelerate the stress release/redistribution.…”
Section: Local Slippage Accumulation Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Baek [27] determined the loosening mechanism of threaded fasteners for complex structures through finite element analysis and experiments. Gong [28] has studied the key factors that affect the loosening of the bolted connection in the finite element analysis. The bolt model with the thread rise angle provided more detailed data for the analysis of the process of the loosened bolted connection, but the huge calculation caused by this can easily lead to the phenomenon of non-convergence in the analysis, which makes the finite element simulation analysis slightly insufficient in practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…e limit value of the safety margin is determined by the user. Gong and Liu developed a three-dimensional finite element model to investigate the effects of the preload generation, vibration parameter, and material model on the loosening [7] and identified the critical transverse force for initiating loosening [8]. Zhao et al [9] proposed a simplified numerical model of bolt slipping for simulating SJs and better capturing the slipping phenomenon.…”
Section: Introductionmentioning
confidence: 99%